Self-Reported Patient Compliance With Physician Advised Lifestyle Behavior Changes Among Adults With Musculoskeletal Conditions - Chen, Jason N.; Dennis, Jeff A.; St. John, Julie A.; Shen, Chwan-Li (Frontiers in Public Health, 2022)
Introduction Approximately half of adult Americans suffer from musculoskeletal disorders (MSD). Significant risk factors for musculoskeletal disorders include poor diet, obesity, and insufficient physical activity. Studies show that lifestyle change education and interventions reduce MSD risk factors. However, little is known about the relationship between physician advice for behavior change and reported behavior change by MSD patients. This study explored the association between physician advice for lifestyle change and reported change in MSD patients, as well as the effects that patient education levels have on compliance. Methods This study used data from the 2017 National Health Interview Survey, a nationally representative cross-sectional survey of non-institutionalized US adults. The research team limited analysis to adults who reported a limitation due to musculoskeletal problems (n = 2,672). Outcomes included physician recommendations to increase physical activity, reduce fat/calories, or lose weight, and whether they enacted these behavioral changes. Adjusted logistic regression models examined whether compliance with doctor's instructions differed by education level. Results Adjusted models show patients advised to change physical activity, diet, and weight were more likely to report attempted behavior change. Education was positively associated with likelihood of complying with physician advice to increase physical activity. Among patients not advised to change behaviors by a physician, education was positively associated with current behavior change attempts. Conclusion This study suggests that physician recommendations are relevant predictors of reported behavior change in individuals with MSD. Although education plays an important role in this association, the relationship is complex and multifaceted. Future studies should explore how compliance may be impacted by other factors, such as physician message type.